Efficacy and Safety of Ceritinib (450 mg/d or 600 mg/d) With Food Versus 750-mg/d Fasted in Patients With ALK Receptor Tyrosine Kinase (ALK)-Positive NSCLC: Primary Efficacy Results From the ASCEND-8 Study - Cho, Byoung Chul; Obermannova, Radka; Bearz, Alessandra; McKeage, Mark; Kim, Dong-Wang; Batra, Ullas; Borra, Gloria; Orlov, Sergey; Kim, Sang-We; Geater, Sarayut L; Postmus, Pieter E; Laurie, Scott A; et al. (Journal of thoracic oncology, 2019)
INTRODUCTION: In an earlier report of the ASCEND-8 study (open-label, phase I, three-arm study, treatment-naive patients and pre-treated patients with advanced/metastatic NSCLC), it was shown that ceritinib 450 mg with food had comparable exposure and better gastrointestinal tolerability than 750-mg fasted. METHODS: Here, we report efficacy and updated safety data from primary efficacy analysis of the ASCEND-8 study. Key secondary endpoints were overall response rate and duration of response, assessed by blinded independent review committee (BIRC) using Response Evaluation Criteria in Solid Tumors 1.1. RESULTS: In total, 306 patients were randomized to ceritinib 450-mg fed (n = 108) or 600-mg fed (n = 87) or 750-mg fasted (n = 111), of which 304 patients were included in safety analysis and 198 treatment-naive patients (ALK receptor tyrosine kinase [ALK]-positive by immunohistochemistry) were included in the efficacy analysis (450-mg fed [n = 73], 600-mg fed [n = 51], and 750-mg fasted [n = 74]). The BIRC-assessed overall response rate was 78.1% (95% confidence interval [CI]: 66.9-86.9), 72.5% (95% CI: 58.3-84.1), and 75.7% (95% CI: 64.3-84.9), respectively; and the median duration of response (months) by BIRC was not estimable (NE) (95% CI: 11.2-NE), 20.7 (95% CI: 15.8-NE), and 15.4 (95% CI: 8.3-NE), respectively. Based on the safety analysis (n = 304), the 450-mg fed arm showed the highest median relative dose intensity (100% versus 78.5% versus 83.7%), lowest proportion of patients with dose reductions (24.1% versus 65.1% versus 60.9%), and lowest proportion of patients with gastrointestinal toxicities (75.9% versus 82.6% versus 91.8%). CONCLUSION: Ceritinib at a dose of 450 mg with food compared to 750-mg fasted showed consistent efficacy and less gastrointestinal toxicity.
Keywords: Fasting; nádory jater; nádory plic; nádory mozku; nemalobuněčný karcinom plic; Food effect; Lung Neoplasms; Humans; nádory kostí; lidé středního věku; pyrimidiny; Brain Neoplasms; Sulfones; Carcinoma, Non-Small-Cell Lung; maximální tolerovaná dávka; Bone Neoplasms; Aged; mladý dospělý; dospělí; Antineoplastic Agents; Female; senioři; lidé; Liver Neoplasms; kritéria léčebné odpovědi; Adult; Anaplastic Lymphoma Kinase; Follow-Up Studies; ženské pohlaví; ALK receptor tyrosine kinase; Male; NSCLC; Middle Aged; anaplastická lymfomová kináza; sulfony; prognóza; Aged, 80 and over; protinádorové látky; Gene Rearrangement; Young Adult; omezení příjmu potravy; senioři nad 80 let; Maximum Tolerated Dose; genová přestavba; Food; Pyrimidines; mužské pohlaví; Response Evaluation Criteria in Solid Tumors; Ceritinib; potraviny; Prognosis; následné studie